Sickness Absence, Works Councils, and Personnel Problems. Evidence from German Individual and Linked Employer-Employee Data - Daniel Arnold; Tobias Brändle; Laszlo Goerke (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Using both household and linked-employer-employee data we study the effects of works councils on individual sickness absence rates and a subjective measure of personnel problems due to absenteeism in Germany. We find that the existence of a works council is positively correlated with the incidence of absence and the amount of days being absent. Further, personnel problems due to absenteeism are more likely in plants in which there is a works council. We cannot reject the hypothesis, however, that self-selection of employees or firms gives rise to this relationship between absenteeism and works councils.
Keywords: J53; I18; M54; 330